Stymulacja nauki uczniów polskich i czeskich za pomocą narzędzi e-learningowych - Ogrodzka-Mazur, Ewa; Szafrańska, Anna; Malach, Josef; Chmura, Milan (Studia Edukacyjne, 2018)
The article is a result of the collaboration between Polish and Czech scientists who explore academic teachers’ application of resources from the e-learning environment. The presented studies were conducted in 2015-2016 within the IRNet project – International research network for study and development of new tools and methods for advanced pedagogical science in the field of ICT instruments, e-learning and intercultural competences in Poland (University of Silesia in Katowice, Faculty of Ethnology and Educational Science in Cieszyn) and the Czech Republic (University of Ostrava, Pedagogical Faculty). The research was aimed at learning the opinions of academic teachers on their preparation for distance classes and for the stimulation of students’ learning process. The research applied a constructivist perspective, which highlighted the learner’s activity resulting in the subject building their educational reality (in the educational process). Due to the comparative nature of the research, it invoked Harold J. Noah’s model of comparing the quality of University education. The text discusses cases of Poland and the Czech Republic.